1996
DOI: 10.1007/bf02500034
|View full text |Cite
|
Sign up to set email alerts
|

SP1 binding site polymorphism in the col1A1 gene is associated with BMD: The rotterdam study

Abstract: Vitamin D treatment in elderly populations has in recent years been shown to reduce hip fractures. The aim of the present study was to perform a longitudinal study of calcidiol (25 OH vitamin D) in a community based population and to analyze correlations to J risk factors for osteoporosis. PoPulation and methods. The study is a part of the geriatric and gerontological population studies in G6teborg, Sweden. A randomized population of men and women born 1901/02 has been investigated with regular intervals since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Individuals with the low bone density‐associated ss genotype were 10 times more frequent in the osteoporotic group (14.3%) when compared with the control group (1.4%), reflecting a relative risk of 11.83 for the presence of osteoporotic vertebral fracture in those with the rare ss genotype. The over‐representation of s alleles in osteoporotic patients from Denmark are consistent with those found in osteoporotic U.K. women 14 , 20 and in osteoporotic Dutch women, 21 suggesting that the COLIA1 polymorphism has potential clinical value as a predictor of osteoporotic vertebral fracture in diverse populations. A preliminary study by Hustmeyer et al published in abstract form 22 did not find any over‐representation of ss in the osteoporotic group.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Individuals with the low bone density‐associated ss genotype were 10 times more frequent in the osteoporotic group (14.3%) when compared with the control group (1.4%), reflecting a relative risk of 11.83 for the presence of osteoporotic vertebral fracture in those with the rare ss genotype. The over‐representation of s alleles in osteoporotic patients from Denmark are consistent with those found in osteoporotic U.K. women 14 , 20 and in osteoporotic Dutch women, 21 suggesting that the COLIA1 polymorphism has potential clinical value as a predictor of osteoporotic vertebral fracture in diverse populations. A preliminary study by Hustmeyer et al published in abstract form 22 did not find any over‐representation of ss in the osteoporotic group.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, the lack of an association between COLIA1 genotype and BMD in the controls, which we found in this study, is in accordance with recent data, published in abstract form, which have shown no association between COLIA1 genotype and bone mass in certain populations 25–27 . Nonetheless, data from other large population‐based cohorts in The Netherlands 21 and France 26 has shown an association between COLIA1 genotype and BMD, while also showing that the effect is relatively small. Since the number of individuals studied here in the control and fracture groups was relatively small and comprised of both males and females, we may have had limited power to detect genotype differences in BMD.…”
Section: Discussionmentioning
confidence: 96%
“…Some researchers have investigated the polymorphism of the genes encoding receptors for vitamin D or oestrogens and the genes for collagen type I or interleukin (IL)-6 (a cytokine involved in the differentiation of osteoclasts) [24,[26][27][28]. While there is still considerable controversy on the genetic determinism of osteoporosis [24,75], the most promising finding remains the identification of a polymorphism in the gene COLIA1 which encodes the type I collagen and mutations of this gene have been associated with a low BMD [29,30].…”
Section: Genetic Factorsmentioning
confidence: 99%